2021
DOI: 10.1186/s13071-021-05006-8
|View full text |Cite
|
Sign up to set email alerts
|

Granulocytic myeloid-derived suppressor cells inhibit T follicular helper cells during experimental Schistosoma japonicum infection

Abstract: Background CD4+ T helper (Th) cells play critical roles in both host humoral and cellular immunity against parasitic infection and in the immunopathology of schistosomiasis. T follicular helper (Tfh) cells are a specialized subset of Th cells involved in immunity against infectious diseases. However, the role of Tfh cells in schistosome infection is not fully understood. In this study, the dynamics and roles of Tfh cell regulation were examined. We demonstrated that granulocytic myeloid-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…With the progression of schistosomiasis, the expression of Programmed Cell Death Protein 1 (PD‐1) on T follicular helper (Tfh) cells and PD‐L1 from myeloid‐derived suppressor cells increases. Granulocytic myeloid‐derived suppressor cells might regulate Tfh cells through the PD‐1/PD‐L1 pathway 15 . A recent study has shown that PD‐1‐deficient Tregs expressed larger amounts of adenosine receptors CD39 and CD73 that were crucial for Treg‐mediated immunosuppression 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the progression of schistosomiasis, the expression of Programmed Cell Death Protein 1 (PD‐1) on T follicular helper (Tfh) cells and PD‐L1 from myeloid‐derived suppressor cells increases. Granulocytic myeloid‐derived suppressor cells might regulate Tfh cells through the PD‐1/PD‐L1 pathway 15 . A recent study has shown that PD‐1‐deficient Tregs expressed larger amounts of adenosine receptors CD39 and CD73 that were crucial for Treg‐mediated immunosuppression 16 …”
Section: Introductionmentioning
confidence: 99%
“…Granulocytic myeloidderived suppressor cells might regulate Tfh cells through the PD-1/PD-L1 pathway. 15 A recent study has shown that PD-1-deficient Tregs expressed larger amounts of adenosine receptors CD39 and CD73 that were crucial for Tregmediated immunosuppression. 16 Sj16 was first identified from S. japonicum as a homolog of Sm16 from S. mansoni, 17 and was reported to be upregulated in the parasite stages of cercariae, eggs, miracidia, sporocysts, and lung-stage schistosomula.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the proportion and activation of CD4 + T cells and CD8 + T cells decreased significantly with the increase of MDSCs at 6-7 weeks after infection (Fig 2). These results suggested that pulmonary CD11b + Gr1 + cells from S. japonicum-infected mice have a suppressive function and are considered to be MDSCs [16,35].…”
Section: Discussionmentioning
confidence: 91%
“…These results suggested that pulmonary CD11b + Gr1 + cells from S . japonicum -infected mice have a suppressive function and are considered to be MDSCs [ 16 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…A more recent study by Zhang et al (2021) showed that Myeloid-Derived-Suppressor-Cells (MDSC) in S. japonicum infected murine models were able to regulate the T-follicular -helper cells (Tfh-cells) proliferation via PD-1/PD-L1 axis (62). The authors reported that SEA and SWA could induce the generation of Tfh-cells in which the PD-1 expression rises along with PD-L1 in MDSC.…”
Section: Pd-l1 In Infectionsschistosomiasis Casementioning
confidence: 99%